Іntroduction of the usufruct institution in Ukraine - Pankivskyi , Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The dynamics of the development of private legal relations, the opening of the land market in our country dictate the need for an in-depth study of already existing foreign experience in the field of real rights to other people's property, in particular usufruct, with the aim of its reception in the civil legislation of Ukraine.The article is devoted to usufruct, according to which a thing that belongs to one person on a legal basis is transferred for use by another, in order to satisfy the property interests of both the owner of the thing and the user of someone else's property.The legal construction of usufruct has been known since the time of the Roman Empire. Currently, the specified real right to someone else's property is an independent institution in the legal systems of many democratic, highly developed European countries.At the present time, the first steps are being taken in Ukraine on the way to the introduction of the usufruct institution into civil law. One of the important steps was the development of the Concept of updating the Civil Code of Ukraine, in which, in order to bring the Code into line with the real state of social relations, among other things, the introduction of the usufruct institution was proposed.The article reveals the main features of usufruct as a property right in general, and as a separate limited right to someone elses property with its own characteristics. On their basis, attention is drawn to the fact that there are legal constructions in the domestic legislation, with the help of which there is the possibility of using someone elss property similar to usufruct. Such a right is, in particular, emphyteusis - the right to use someone elseєs land for agricultural purposes.As a result of the analysis of the legal nature of limited rights to use someone else's property, regulated by legislation, it was concluded that the object of these rights is, first of all, immovable property. The issue of use of other types of other people's property  can be settled by the parties by concluding contracts not provided for by law (unnamed), which is ensured by one of the main principles of civil legislation - freedom of contract. At the same time, the author comes to the conclusion that the introduction of the institution of usufruct into the civil law of Ukraine will definitely contribute to the expansion of opportunities for the use of all types of things in circulation.